2006
DOI: 10.1103/physrevd.73.104038
|View full text |Cite
|
Sign up to set email alerts
|

Realistic exact solution for the exterior field of a rotating neutron star

Abstract: A new six-parametric, axisymmetric and asymptotically flat exact solution of Einstein-Maxwell field equations having reflection symmetry is presented. It has arbitrary physical parameters of mass, angular momentum, mass-quadrupole moment, current octupole moment, electric charge and magnetic dipole, so it can represent the exterior field of a rotating, deformed, magnetized and charged object; some properties of the closed-form analytic solution such as its multipolar structure, electromagnetic fields and singu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…Whenever an analytic metric is used to mimic the gravitational field of a realistic neutron star [13], and then this metric is used to reproduce various observables related to neutron stars [24], it is important to use the right moments in order to build a faithful analytic metric; otherwise any physical conclusion inferred by the analytic metric would be off [23]. If quantitative conclusions are drawn while using wrong moments in the analytic metric, they should be taken into account with some reservation.…”
Section: Consequences Of Evaluating the Right Momentsmentioning
confidence: 99%
“…Whenever an analytic metric is used to mimic the gravitational field of a realistic neutron star [13], and then this metric is used to reproduce various observables related to neutron stars [24], it is important to use the right moments in order to build a faithful analytic metric; otherwise any physical conclusion inferred by the analytic metric would be off [23]. If quantitative conclusions are drawn while using wrong moments in the analytic metric, they should be taken into account with some reservation.…”
Section: Consequences Of Evaluating the Right Momentsmentioning
confidence: 99%
“…Kluźniak et al 1990;Shibata & Sasaki 1998;Pachón et al 2006Pachón et al , 2012Bakala et al 2012;Gutierrez et al 2013). It has been shown that for geodesic motion, these are well described by formulae derived considering NS spacetime approximated by the Hartle-Thorne metric (Hartle & Thorne 1968;Abramowicz et al 2003;Berti et al 2005).…”
Section: Behaviour Of Isco Radius and Ns Compactnessmentioning
confidence: 82%
“…In this regard, one can think about potential importance the equatorially symmetric configurations of the extended triple-Kerr [37,38] and quadruple-Kerr [39] solutions might have for astrophysical applications in the future. …”
Section: Discussionmentioning
confidence: 99%